Artificial intelligence and communication techniques in industry 5.0 - Bansal, Payal; Kumar, Rajeev 1985-; Kumar, Ashwani 1989-; Dasig, Daniel D. (Advances in manufacturing, design and computational intelligence techniques, 2025)
"The text highlights the role of artificial intelligence in driving innovation, productivity, and efficiency. It further covers applications of artificial intelligence for digital marketing in Industry 5.0 and discusses data security and privacy issues in artificial intelligence, risk assessments, and identification strategies. This book: Discusses the role of artificial intelligence applications for digital manufacturing in Industry 5.0. Presents blockchain methods and data-driven decision-making with autonomous transportation. Covers reinforcement learning algorithm and highly predicted models for accurate data analysis in industry automation. Highlights the importance of robust authentication mechanisms and access control policies to protect sensitive information, prevent unauthorized access, and enable secure interactions between humans and machines. Explains attack pattern detection and prediction which play a crucial role in ensuring the security of business systems and networks. It is primarily written for senior undergraduates, graduate students, and academic researchers in the fields of electrical engineering, electronics and communication engineering, computer engineering, industrial engineering, manufacturing engineering, and production engineering"--